The Spiritual Well-Being Scale: Psychometric Evaluation of the Shortened Version in Czech Adolescents - Malinakova, Klara (Journal of religion and health, 2017)
The aim of this study was to psychometrically evaluate the shortened version of the Spiritual Well-Being Scale (SWBS) in Czech adolescents. A nationally representative sample of 4217 adolescents participated in the 2014 Health Behaviour in School-aged Children survey. The internal consistency of the SWBS was assessed using Cronbach’s alpha (α) and Mean Inter-Item Correlation (MIIC) values. The factor structure was evaluated using principal component analyses. After adjustment, our new seven-item version of the scale supports a two-factorial model of the SWBS with satisfactory internal consistency (α = 0.814, MIIC = 0.379). This version of the SWBS is suitable for measuring spiritual well-being in a secularising environment.